A taxonomic synopsis of Brazilian Chloraeinae (Orchidaceae: Orchidoideae) - Buzatto, Cristiano Roberto; Sanguinetti, Agustín; Romero-González, Gustavo A.; van Den Berg, Cássio; Singer, Rodrigo B. (Phytotaxa, 2014)
A taxonomic synopsis of Brazilian Chloraeinae (Orchidaceae) is presented. Artificial keys to separate the genera and species are included. Vegetative and floral features of all species are described and illustrated with drawings and photographs, and data on their distribution, phenology and ecology are presented. Two lectotypes and one neotype are proposed. The presence of Bipinnula biplumata, B. montana, B. penicillata and Chloraea membranacea in Brazil is confirmed, and Bipinnula gibertii is reported for the first time from this country.